2014
DOI: 10.1039/c4tc01214c
|View full text |Cite
|
Sign up to set email alerts
|

Charge compensation in RE3+ (RE = Eu, Gd) and M+ (M = Li, Na, K) co-doped alkaline earth nanofluorides obtained by microwave reaction with reactive ionic liquids leading to improved optical properties

Abstract: 2014Charge compensation in RE3+ (RE = Eu, Gd) and M+ (M = Li, Na, K) co-doped alkaline earth nanofluorides obtained by microwave reaction with reactive ionic liquids leading to improved optical properties Journal of Materials Chemistry C,Cambridge : Royal Society of Chemistry -RSC,v. 2, n. 44, p. 9439-9450, 2014 http://www.producao.usp.br/handle/BDPI/50592 (REDOR) studies, reveal distinct local fluoride environments, the populations of which are discussed in relation to spatial distribution and clustering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Rare earth doped barium halide single crystals are also used as scintillators for X-ray and gamma ray detections [11]. Lorbeer et al [12] reported the introduction of trivalent lanthanide ions into the divalent alkaline earth fluoride lattice and observed that the cubic crystal system doesn't changed. This substitution requires charge compensation and hence leads to the defects such as interstitial fluoride ions and or defect aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth doped barium halide single crystals are also used as scintillators for X-ray and gamma ray detections [11]. Lorbeer et al [12] reported the introduction of trivalent lanthanide ions into the divalent alkaline earth fluoride lattice and observed that the cubic crystal system doesn't changed. This substitution requires charge compensation and hence leads to the defects such as interstitial fluoride ions and or defect aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…An easy and convenient approach is to dope impurities in matrixes to enhance emission or obtain multi-color emission141516. The impurity can be any elements for the non-isovalent doping, such as trivalent rare earth and monovalent alkaline metal ions1718. This method has been extensively investigated in luminescent compounds, photo-catalysts, and magnetic materials.…”
mentioning
confidence: 99%
“…Decomposition of transition-metal amidinates in [BMIm][BF 4 ] yielded metal fluoride nanoparticles for Mn, Fe and Co [ 63 ]. The reaction of metal acetate (hydrate) precursors in ethylene glycol and an excess of [BMIm][BF 4 ] gave fluoride nanoparticles [ 67 ]. Mesoporous carbon/iron carbide hybrids were synthesized using mesoporous silica as template and the ionic liquid [BMIm][FeCl 4 ] as carbon and iron source [ 68 ].…”
Section: Resultsmentioning
confidence: 99%